2022
DOI: 10.1029/2022gl097786
|View full text |Cite
|
Sign up to set email alerts
|

Regional Map of Molecular Water at High Southern Latitudes on the Moon Using 6 μm Data From the Stratospheric Observatory for Infrared Astronomy

Abstract: A map of surface molecular water was derived from long slit spectroscopy of the south polar region of the Moon using the Faint Object infraRed CAmera for the SOFIA Telescope spectrometer on the Stratospheric Observatory for Infrared Astronomy. Mean water abundances detected are about 250 μg/g over that of a mare reference surface at Mare Fecunditatis. Water abundances are locally anticorrelated with temperature. The distribution of water is consistent with derivation of water from pre‐existing hydroxyl subsequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 32 publications
2
17
1
Order By: Relevance
“…A 6.1 μm spectral feature uniquely detects H 2 O (as opposed to just the O-H bond) because it arises from an H-O-H bending mode that requires all three atoms of the molecule. This feature was detected at a sunlit region near the Clavius crater (Honniball et al 2021) and has been confirmed over a larger area with more recent measurements (Honniball et al 2022). In this work, we present the results for part of the southern polar region, in order to determine whether the 6.1 μm water feature correlates with other localized structures.…”
Section: Introductionsupporting
confidence: 68%
See 3 more Smart Citations
“…A 6.1 μm spectral feature uniquely detects H 2 O (as opposed to just the O-H bond) because it arises from an H-O-H bending mode that requires all three atoms of the molecule. This feature was detected at a sunlit region near the Clavius crater (Honniball et al 2021) and has been confirmed over a larger area with more recent measurements (Honniball et al 2022). In this work, we present the results for part of the southern polar region, in order to determine whether the 6.1 μm water feature correlates with other localized structures.…”
Section: Introductionsupporting
confidence: 68%
“…Water molecules were recently detected even on the sunlit surface of the Moon (Honniball et al 2021(Honniball et al , 2022, and this paper extends those results to present the first well-sampled, wide-area images of localized variations in water abundance. A 6.1 μm spectral feature uniquely detects H 2 O (as opposed to just the O-H bond) because it arises from an H-O-H bending mode that requires all three atoms of the molecule.…”
Section: Introductionsupporting
confidence: 65%
See 2 more Smart Citations
“…Honniball et al. (2022) later detected surface abundance from the 6 μm feature that exceeds the amount measured for the lunar exosphere, suggesting that the feature is caused by molecular water trapped in an impact glass. In situ observations by the Chang’E−5 lander provide evidence for hydration, but cannot conclusively state whether the feature is provided by hydroxyl or molecular water (Lin et al., 2022).…”
Section: Introductionmentioning
confidence: 97%